THE PHARMACEUTICAL PROFILE CHARACTERIZATION OF TELMISARTAN HYDROCHLORIDE CRYSTAL HYDRATE AND ANHYDRATE - Rahmah, Ridha
Telmisartan is an antihypertensive drug belonging to the Angiotensin Receptor Blockers (ARB) class, categorized as Class II in the Biopharmaceutical Classification System (BCS). This means the drug has high permeability but low solubility. Telmisartan was converted into its HCl salt form and then formed into an anhydrate. This study aims to characterize the pharmaceutical profile of telmisartan HCl anhydrate compared to telmisartan HCl trihemihydrate. The anhydrate salt obtained was characterized using thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and powder X-ray diffractometry (PXRD) to determine its characteristics. Subsequently, tests were conducted to evaluate solubility, intrinsic dissolution rate, particle size distribution, tabletability, and flow rate. The instrumental analysis confirmed the formation of telmisartan HCl anhydrate. Telmisartan HCl anhydrate increased solubility by 1,4 times compared to the hydrate form and 18,9 times compared to telmisartan, improving the intrinsic dissolution rate by 4,3 times compared to the hydrate form. However, the flow rate was poorer than the hydrate form, and tabletability did not show a significant difference (P>0,05) compared to the hydrate form.